On any topic? Topics of publications of investigative journalism and journalistic intervention in the local press (on the examples of Poland and the USA) - Adamczyk, Wojciech (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2015)
The author raises an interesting subject, hitherto unexplored comprehensively in American and Polish media studies, namely, the problem of topics of investigative journalism and journalistic intervention at the level of local newspaper publishers. In local media, just as in national media, disclosure of corruption and misconduct of local government happens quite rarely. Additionally, the checking activity – as the watchdog function of the press – is present in the Polish reality only in some local commercial media which are independent from local government. The author discusses the impact of the media’s checking function for the selection of topics by local investigative journalists and the nature of the activities of local political and business decision-makers limiting the subjects addressed by investigative reporters. A comparative analysis relates the problems of the functioning of local government and local communities which are aired in articles published by investigative journalists and journalistic intervention. For the comparison, articles recognised by the jury of the Pulitzer Prize for investigative journalism 1926–2015 and texts submitted and recognised in the “Local Press” competition 2012–2013 organised by the Association of Local Newspapers were used.

Autor podjął ciekawy, chociaż do tej pory niezbadany kompleksowo na gruncie amerykańskiego i polskiego medioznawstwa problem tematyki poruszanej w publikacjach dziennikarstwa śledczego i interwencyjnego na poziomie lokalnych wydawnictw prasowych. Podobnie jak w mediach ogólnokrajowych ujawnianie afer i nagłaśnianie niewłaściwych zachowań władzy zdarza się dosyć rzadko w mediach lokalnych, a działalność kontrolna w ramach watchdog function of the press występuje w polskich realiach tylko w nielicznych lokalnych mediach komercyjnych, niezależnych od organów samorządowych. Autor omawia wpływ funkcji kontrolnej mediów na dobór tematyki przez lokalnych dziennikarzy śledczych oraz charakter działań lokalnych decydentów politycznych i biznesowych ograniczających tematykę podejmowaną przez reporterów dochodzeniowych. Analizie porównawczej poddano problemy funkcjonowania organów samorządowych oraz społeczności lokalnych nagłaśniane w publikacjach demaskatorskich i interwencyjnych. Do porównania wykorzystano artykuły o tematyce lokalnej nagrodzone Pulitzer Prize za dziennikarstwo śledcze w latach 1926–2015 oraz materiały nadesłane i nagrodzone w latach 2012–2013 w konkursie “Local Press”, organizowanym przez Stowarzyszenie Gazet Lokalnych.
Na każdy temat? Tematyka publikacji dziennikarstwa śledczego i interwencyjnego w prasie lokalnej (na przykładzie Polski i USA)
Keywords: local press; investigative journalism; journalistic intervention; the subject matter of publication; prasa lokalna; dziennikarstwo śledcze; dziennikarstwo interwencyjne; tematyka publikacji